2006
DOI: 10.1016/j.febslet.2006.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Polo‐like kinase 1 regulates mitotic arrest after UV irradiation through dephosphorylation of p53 and inducing p53 degradation

Abstract: Ultraviolet (UV) irradiation can result in cell cycle arrest. The reactivation of Polo-like kinase 1 (Plk1) is necessary for cell cycle reentry. But the mechanism of how Plk1 regulates p53 in UV-induced mitotic arrest cells remained elusive. Here we find that UV treatment leads HEK293 cells to inverse changes of Plk1 and p53. Over-expression of Plk1 rescue UV-induced mitotic arrest cells by inhibiting p53 activation. Plk1 could also inhibit p53 phosphorylation at Ser15, thus facilitates its nuclear export and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 31 publications
(49 reference statements)
0
29
0
Order By: Relevance
“…Similarly, Liu and Erikson (25) described that Plk1 depletion stabilizes p53 in HeLa cells. In support with this notion, Chen et al (36) found that Plk1 inhibits UV-mediated phosphorylation of p53 at Ser-15 and thereby facilitates its nuclear export and proteolytic degradation.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, Liu and Erikson (25) described that Plk1 depletion stabilizes p53 in HeLa cells. In support with this notion, Chen et al (36) found that Plk1 inhibits UV-mediated phosphorylation of p53 at Ser-15 and thereby facilitates its nuclear export and proteolytic degradation.…”
Section: Discussionmentioning
confidence: 87%
“…Cdc25C, a phosphatase known to be activated by Plk1-dependent phosphorylation, seems to mediate the Plk1-induced dephosphorylation of p53, since Cdc25C is found in a complex with Plk1 and p53 in HEK293 cells. 40 In light of the data reviewed within this article, Plk1 contributes to the regulation of its own gene expression by the ability to render p53 inactive.…”
Section: Regulation Of Transcriptionally Active Proteins By Plk1mentioning
confidence: 99%
“…39 In contrast, overexpression of Plk1 decreases the Ser 15 phosphorylation level of p53 in UV-induced M-phase arrested HEK293 cell. 40 Since phosphorylation of Ser 15 contributes to increased stability of the p53 protein, this scenario also results in inactivation of p53 by Plk1. Cdc25C, a phosphatase known to be activated by Plk1-dependent phosphorylation, seems to mediate the Plk1-induced dephosphorylation of p53, since Cdc25C is found in a complex with Plk1 and p53 in HEK293 cells.…”
Section: Regulation Of Transcriptionally Active Proteins By Plk1mentioning
confidence: 99%
See 2 more Smart Citations